Solar-Powered Charge Stations: LCA Thinking - Chan, E.; Erickson, Larry E.; Boguski, Terrie K.; Leven, Blase A.; Natarajan, Bala (Kansas State University, 2012)
Life cycle assessment shows that solar energy has lower greenhouse gas emissions compared to coal and natural gas. There are air quality benefits associated with the electrification of transportation. Solar-powered charge stations and the electrification of transportation reduce GHGs and improve air quality. Introducing plug-in hybrid electric vehicles (PHEVs) and electric vehicles (EVs) can potentially reduce dependence on foreign oil, and introducing more charge stations can help them penetrate the automobile market. Further research is needed to develop the decision support tools.
Keywords: Solar power; Charge station; Electric vehicle; Triple bottom line; Decision tool; Life cycle assessment